THE INFLUENCE OF PRODUCT INNOVATION, SOCIAL MEDIA MARKETING, AND LOCATION ON PURCHASE DECISIONS AT TEH POCI GANA(A Case Study of Teh Poci Gana in Bantul, Yogyakarta) - Nyoman Parartha Deswara Evaganna; Putu Saroyini Piartrini (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The background of this study is based on the phenomenon of a significant decline in the sales turnover of Teh Poci Gana due to intense competition from similar businesses within its operational area. This study aims to examine and explain the influence of product innovation, social media marketing, and location on purchase decisions at Teh Poci Gana. The research was conducted at Teh Poci Gana located in Dusun Ngebel, Tamantirto, Bantul Regency, Yogyakarta. This study employs a quantitative approach with an associative research design. The population consists of all consumers who have previously purchased products from Teh Poci Gana. The sampling technique used was purposive sampling, involving 200 respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis, classical assumption tests, and hypothesis testing (t-test and F-test) with the assistance of SPSS version 25. The results show that: (1) product innovation has a positive and significant effect on purchase decisions, indicating that better product innovation leads to higher consumer purchase decisions; (2) social media marketing has a positive and significant effect on purchase decisions, suggesting that effective promotion through social media can increase purchase decisions; and (3) location has a positive and significant effect on purchase decisions, where ease of access and visibility significantly contribute to consumers’ purchasing decisions. Simultaneously, these three independent variables have a significant effect on purchase decisions, with a contribution of 23.3%.